Cutaneous Collagenous Vasculopathy: Report of Two Cases Presenting as Disseminated Telangiectasias and Review of the Literature. (September 2017) - Bondier, Laure; Tardieu, Mathilde; Leveque, Perrine; Challende, Isabelle; Pinel, Nicole; Leccia, Marie T.
Abstract : Abstract: Cutaneous collagenous vasculopathy is a recently described idiopathic microangiopathy characterized by acquired diffuse cutaneous telangiectasias and specific histological features: dilated capillaries in the superficial dermis, with walls thickened by hyaline material containing collagen IV by immunohistochemistry. The authors describe 2 cases and review all cases reported in the literature to date, 34 cases including our own. Cases were mainly observed in women (sex ratio 0.41), median age 63.5 (16–85). Hypertension and diabetes seem more frequent in these patients than in the general population. Typical clinical presentation is fine hair telangiectasias appearing on the lower limbs and progressing toward the trunk and upper limbs, sparing the face. Facial and neck involvement are however reported. When faced with isolated acquired diffuse cutaneous telangiectasias, clinicians should perform a skin biopsy to rule out cutaneous collagenous vasculopathy.